THE ECONOMIC POTENTIAL OF WASTE MANAGEMENT IN PENYENGAT ISLAND TOURISM, TANJUNGPINANG CITY, RIAU ISLAND PROVINCE, INDONESIA - Zainul Ikhwan; R. Hamdani Harahap; Lita Sri Andayani; Miswar Budi Mulya (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Penyengat Island is one of the tourist objects for Islamic religion and culture, and history in Tanjungpinang City, Riau Islands. The natural beauty and cultural heritage owned by Penyengat Island is a tourist attraction, so that the number of tourist visits with directed or tourism purposes. Tourism activities in the Penyengat Island area have a positive impact. However, besides that, tourism activities negatively impact the environment, namely, tourism waste in the form of garbage that can reduce the environment’s quality and sustainability. Penyengat Island also has limited land for waste management and is an island with a small area of less than 2 square kilometers. The research aims to identify the potential for waste generation from tourism activities in the Penyengat Island area, identify waste management in the Penyengat Island area, estimate the economic costs and benefits of alternative waste management in the Penyengat Island area, and estimate the costs that businesses and tourists are willing to pay in the Island area. Stingers against the implementation of waste management to preserve the area. The method used is descriptive analysis, Benefit Transfer, and Contingent Valuation Method. The results showed that most tourism waste originating from tourists in one year was in plastic waste, while most of the tourist waste originating from business actors was organic waste. Waste management in the Penyengat Island area is currently still using a waste transportation collection system, with recommendations for alternative waste management to be carried out in the Penyengat Island area, namely the construction of TPS 3R (reuse, reduce, recycle). The estimated cost of waste management using the TPS 3R system consists of an investment cost of IDR 750,000,000 and an annual operational cost of IDR 62,747,000. The estimated economic benefits resulting from the sale of waste in the TPS 3R system are IDR 80,791,002/year. The value of willingness to pay tourists and business actors to implement waste management can meet the operational costs and investment costs of TPS 3R of 27.31%. Therefore, the TPS 3R project deserves to be implemented.